PERSEPSI DAMPAK PERUBAHAN ADMINISTRASI WILAYAH TERHADAP SOSIAL EKONOMI DAN SOSIAL BUDAYA MASYARAKAT KECAMATAN BUKIT INTAN KOTA PANGKAL PINANG - , SITI NURDIANTI ASTUTI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Bukit Intan is one of the district that had the spatial dynamics of administration boundar, Pangkal Pinang regional expantion effect . The changing has some effects on the lives of local communities, social economic, and the shift of cultural values. The purpose of this research is to studying dynamication of changed administration boundary in Bukit Intan distric 2010 and 2011 as an indication of spatial transformation phenomena, as well as the extent on impact of perception and influence society in Bukit Intan. Primary data is the main data used in this study, supplemented with secondary data from some related instances. The method data cultivate in this research is quantitative analysis from the result of questionnaire scoring value. Every variables of indicators assessment has dignity or degree as value to skoring.. The Indicators of welfare and employment opportunities, are indicators to analyze assessment and economic conditions, while the indicators used to assess the social and cultural conditions are stratification and social mobility, transformation and religious norms, and social activity. Then the descriptive analysis is used to add descriptive information to the quantitative data obtained from the field. The results of this research showed that changed of administration boundary in Bukit Intan the indicate of spatial transformation or spatial dynamics in Bukit Intan distric is decline distric area., almost 1 km 2. The effect perception related social economic showed positively perception for society of konstant administration, but didnât give many influences for society of changed administration.While The effect perception related social cultural didnât show many Changes for both of society group.